2008
DOI: 10.1080/01677060701807954
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofHyperkinetic, a β Subunit ofShakerVoltage-Dependent K+Channels, on the Oxidation State of Presynaptic Nerve Terminals

Abstract: The Drosophila Hyperkinetic (Hk) gene encodes a β subunit of Shaker (Sh) K + channels and shows high sequence homology to aldoketoreductase. Hk mutations are known to modify the voltage dependence and kinetics of Sh currents, which are also influenced by the oxidative state of the Nterminus region of the Sh channel, as demonstrated in heterologous expression experiments in frog oocytes. However, an in vivo role of Hk in cellular reduction/oxidation (redox) has not been demonstrated. By using a fluorescent indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…Recent studies have shown that vertebrate Kvβ1 and Kvβ2 not only modulate Kv1α– mediated K + current but also catalyze reduction of aldehydes to alcohols in heterologous expression systems (Weng et al, 2006; Pan et al, 2008). Consistent with the above studies, Hk and gsts1 mutations have recently been shown to alter cellular ROS levels in larval motor terminals (Ueda & Wu 2008). Furthermore, Hk mutant flies are more sensitive to ingestion of the ROS generating agent, paraquat (Wang et al 2000).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Recent studies have shown that vertebrate Kvβ1 and Kvβ2 not only modulate Kv1α– mediated K + current but also catalyze reduction of aldehydes to alcohols in heterologous expression systems (Weng et al, 2006; Pan et al, 2008). Consistent with the above studies, Hk and gsts1 mutations have recently been shown to alter cellular ROS levels in larval motor terminals (Ueda & Wu 2008). Furthermore, Hk mutant flies are more sensitive to ingestion of the ROS generating agent, paraquat (Wang et al 2000).…”
Section: Introductionsupporting
confidence: 74%
“…The gsts1 ; ry 506 and the ry 506 lines were obtained from Bloomington Stock Center (Indiana University, Bloomington, IN). Second-site lethal mutations carried in the original gsts1 ; ry 506 stocks were removed by backcrossing to the ry 506 control line eight or more times (Ueda & Wu, 2008). The ry 506 control and gsts1 04227 ; ry 506 mutant lines were Cantonized 7–8 times further, and part of behavioral and physiological data were taken from these Cantonized stocks.…”
Section: Methodsmentioning
confidence: 99%
“…As the twitching and longevity phenotypes we observed were male specific and intensified with age, we chose to use staged 21 day old adult males for RNA analysis to enhance our opportunity to detect potential changes in gene expression associated with these defects. The putative Dmel\Kdm4A target genes chosen to be assessed were: Shaker (Sh) (Wang et al, 2000; Cirelli et al, 2005), Hyperkinetic (Hk) (Ueda and Wu, 2008), and ether a go-go (Zhong and Wu, 1993) chosen for their involvement in K+ channel function and shown to display a shaking leg phenotype when mutated; park and pink1, involved in Parkinson disease (Greene et al, 2003; Tan and Dawson, 2006); Drosophila Nicotinamidase (D-NAAM), Silent information regulator 2 (Sir2), and rpd3, selected for their involvement in a deacetylase-mediated longevity pathway (Rogina and Helfand, 2004); bent (bt) and myosin heavy chain (Mhc), each involved in muscle function (Redowicz, 2002); defective in the avoidance of repellents (dare) (Freeman et al, 1999), Vap-33-1 (DVAP-33A) (Chai et al, 2008)}, and survival motor neuron (SMN) (Chan et al, 2003) each involved in appropriate neuromuscular junction (NMJ) function; Heat shock protein 22 (Hsp22), the mitochondrial small heat shock protein involved in stress and aging (Morrow et al, 2004); and fruitless ( fru ) involved in male-specific neuron formation that promotes masculinization (Dickson, 2002; Dickson, 2008; Yamamoto, 2008) . The results of our analysis demonstrated that out of the 16 genes assessed, two of the genes (Hsp22 and fru ) were significantly affected, with a marked decrease in mRNA levels for each of them.…”
Section: Resultsmentioning
confidence: 99%
“…8), thermal responses cannot account for the light-induced increase of firing in class IV but not class I dendritic arborization neurons. Moreover, application of 10 μM H 2 O 2 , which elevates the reactive oxygen species (ROS) level in Drosophila larvae20, had no effect on the firing rate of class IV dendritic arborization neurons (Supplementary Fig. 9).…”
Section: Class IV Neurons Tiling Larval Body Wall Sense Lightmentioning
confidence: 99%